(untitled) (CIPEEX, 2025)
The evolution of digital electoral advertising has become an integral component of contemporary democratic processes, reshaping the communication paradigm between political candidates and the electorate. The advent of social media has fundamentally altered the dynamics of political campaigns, enabling more direct and interactive engagement while simultaneously presenting significant legal and ethical challenges, such as the proliferation of disinformation and the misuse of personal data. The unconstrained dissemination of misinformation, amplified by online ecosystems, poses a direct threat to the integrity of electoral procedures, generating profound legal ramifications across electoral, civil, and criminal jurisdictions. Although the Electoral Judiciary has made progress in regulating and supervising digital campaign activities, it continues to face substantial difficulties in keeping pace with the rapid nature of online interactions and the absence of a comprehensive legislative framework specifically designed for the digital domain. This research aims to analyze the legal boundaries of digital electoral advertising and the regulatory measures implemented to mitigate abuses, thereby preserving popular sovereignty and fundamental rights. Utilizing a qualitative and exploratory methodology, the study is based on a meticulous review of bibliographic and documentary sources, including academic literature, legal precedent, and pertinent legislation. The findings reveal that while social media has undeniably democratized political discourse, it has also amplified the risks of manipulation through disinformation and the exploitation of personal data. Consequently, the lacuna left by an outdated and fragmented legal framework creates significant vulnerabilities that undermine the transparency and fairness of electoral competition. Thus, it is imperative to develop and implement effective mechanisms that guarantee the integrity of the democratic process, which requires the synergy of legal modernization, robust institutional oversight, and enhanced civic awareness, all while upholding the principles of transparency, accountability, and freedom of expression.